Prevention of Child Sexual Abuse: Perspectives on Education and Advocacy - Rahmad Rafid; Riski Febria Nurita (Journal of Social Science and Humanities, 2025)
Child sexual abuse is a form of violence that has long-term psychological, physical, and social impacts, requiring attention from society, families, and educational institutions. This study employed a qualitative approach using a literature review method. Data collection was conducted through systematic searches of databases such as Scopus and Google Scholar, validated through source triangulation. Data analysis utilised content analysis to identify themes and patterns. The findings indicated that school-based education is effective in equipping children with self-protection knowledge, although it faces challenges such as limited teacher training, cultural resistance, and insufficient teaching materials. Community-based advocacy has been shown to enhance public awareness, strengthen child protection policies, and reduce stigma against victims, despite obstacles such as weak cross-sector coordination. The study concludes by emphasising the importance of collaboration between education and advocacy in developing sustainable prevention strategies. It recommends the development of culturally sensitive curricula, teacher training programmes, and improved cross-sector coordination to enhance child protection. Practical implications include designing policies that support the synergy of education and advocacy to create a safe environment for children in Indonesia.